2014
DOI: 10.1007/s11033-014-3301-8
|View full text |Cite
|
Sign up to set email alerts
|

RNAi Mediated curcin precursor gene silencing in Jatropha (Jatropha curcas L.)

Abstract: Curcin, a type I ribosomal inhibiting protein-RIP, encoded by curcin precursor gene, is a phytotoxin present in Jatropha (Jatropha curcas L.). Here, we report designing of RNAi construct for the curcin precursor gene and further its genetic transformation of Jatropha to reduce its transcript expression. Curcin precursor gene was first cloned from Jatropha strain DARL-2 and part of the gene sequence was cloned in sense and antisense orientation separated by an intron sequence in plant expression binary vector p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The RNA interference or the RNAi silencing mechanism has emerged as a powerful tool for in planta gene expression manipulation and have been actively adopted in J . curcas [ 71 , 72 , 73 , 74 ]. The mechanism silences the expression of a target gene, introduced through its silencing machinery [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…The RNA interference or the RNAi silencing mechanism has emerged as a powerful tool for in planta gene expression manipulation and have been actively adopted in J . curcas [ 71 , 72 , 73 , 74 ]. The mechanism silences the expression of a target gene, introduced through its silencing machinery [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our studies on C1 transcripts in developing endosperm and curcin proteins in mature endosperm demonstrated that the expression of the C1 gene was efficiently suppressed or completely silenced by the C1 promoter-driven RNAi-mediated gene silencing. Patade et al, (2014) made a 35S promoter-driven RNAi cassette for curcin genes and used Agrobacterium -mediated in planta transformation to produce transformed jatropha plants [ 27 ]. The authors reported that the transcripts of curcin precursor gene were reduced by more than 98 % to undetectable level [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patade et al, (2014) made a 35S promoter-driven RNAi cassette for curcin genes and used Agrobacterium -mediated in planta transformation to produce transformed jatropha plants [ 27 ]. The authors reported that the transcripts of curcin precursor gene were reduced by more than 98 % to undetectable level [ 27 ]. However, the research paper did not provide any data on molecular analysis of stable insertion of T-DNA in jatropha genome, biochemical analysis on curcin proteins in the leaves and seeds of transformed plants.…”
Section: Discussionmentioning
confidence: 99%
“…Some research works have successfully used the RNAi technology to reduce curcins in Jatropha. Suppression of this gene could reduce the curcin up to 98% (Patade et al, 2014;Gu et al, 2015). The cDNA of the gene encoding curcin, i.e., curcin2 was obtained from J. curcas leaves (Tong et al, 2007).…”
Section: Genetic Engineering For Reduction Of Toxic Metabolites In Jamentioning
confidence: 99%